Molten Li Salt Solvate-Silica Nanoparticle Composite Electrolytes with Tailored Rheological Properties - Mayeesha MARIUM; Kazuhide UENO; Kaoru DOKKO; Masayoshi WATANABE (Electrochemistry, 2020)
Nanocomposite electrolytes comprising molten Li salt solvates (MLSs) and inorganic fillers provide liquid-like processing and reasonably high Li ion transport properties. Thus, they can be potentially used as thermally-stable and mechanically-robust electrolytes. In this study, nanocomposite electrolytes exhibiting two distinct non-Newtonian rheological responses, i.e., shear thinning and shear thickening behaviors, were prepared using glyme- and sulfolane-based molten Li salt solvates and hydrophilic fumed silica without any surface modification of the silica. The rheological responses strongly depended on the anionic structure of the MLSs. The MLS-silica composites containing bis(trifluoromethanesulfonyl)amide (TFSA) and BF4 anions formed a shear thinning gel and shear thickening fluid, respectively. The characteristic rheological properties (elastic modulus for the shear thinning gel and the maximum peak viscosity and critical shear rate for the shear thickening system) were extensively tailored by the silica content in addition to the chemical structure of the MLSs, while the changes in their ion transport properties were moderate even in the presence of silica fillers.